1989
DOI: 10.1101/gad.3.3.370
|View full text |Cite
|
Sign up to set email alerts
|

Progressively restricted expression of a homeo box gene within the aboral ectoderm of developing sea urchin embryos.

Abstract: A homeo box-containing gene, Hbox1 is expressed in an unusual and highly conserved spatial pattern in embryos of two different species of sea urchin, Tripneustes gratilla and Strongylocentrotus purpuratus. Hybridization in situ shows that this mRNA accumulates initially throughout the aboral ectoderm; however, between blastula and pluteus stages, the region containing Hbox1 mRNA retracts gradually until only a small area around the vertex is labeled in pluteus larvae. Aboral ectoderm appears cytologically unif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 62 publications
5
39
0
Order By: Relevance
“…Later, the complete sequence of Sp-Hox7 was determined, and it was confirmed to be a paralog of the Hox7 gene group (Martinez et al, , 1999. Sp-Hox7 is expressed in the AE of the blastula stage embryo , and its mRNA retracts to a small area around the apex of the pluteus larva (Angerer et al, 1989). The detailed in situ hybridization results showed that both Sp-Dlx and Sp-Hox7 were first detected in the AE near the vegetal plate of the 20-hpf embryo (Fig.…”
Section: Sp-irxa and Sp-msx Are Co-expressed In The Vegetal Aboral Ecmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, the complete sequence of Sp-Hox7 was determined, and it was confirmed to be a paralog of the Hox7 gene group (Martinez et al, , 1999. Sp-Hox7 is expressed in the AE of the blastula stage embryo , and its mRNA retracts to a small area around the apex of the pluteus larva (Angerer et al, 1989). The detailed in situ hybridization results showed that both Sp-Dlx and Sp-Hox7 were first detected in the AE near the vegetal plate of the 20-hpf embryo (Fig.…”
Section: Sp-irxa and Sp-msx Are Co-expressed In The Vegetal Aboral Ecmentioning
confidence: 99%
“…Further studies showed that Sp-Dlx is expressed in the AE and has a positive feedback relationship with SpIrxA . A Sp-Hox7 fragment was originally isolated from a genomic DNA library (Angerer et al, 1989) using the orthologous gene Hbox1, isolated from the sea urchin Tripneustes gratilla, as a probe (Dolecki et al, 1986). Later, the complete sequence of Sp-Hox7 was determined, and it was confirmed to be a paralog of the Hox7 gene group (Martinez et al, , 1999.…”
Section: Sp-irxa and Sp-msx Are Co-expressed In The Vegetal Aboral Ecmentioning
confidence: 99%
“…Sea urchins also possess a single Hox gene complex containing 10 genes (Martinez et al, 1999). However, in the embryo, only two Hox genes (Hox7 and Hox11/13b) are expressed (Angerer et al, 1989;Dobias et al, 1996). The expression of Hox7 protein is restricted to the aboral ectoderm, and Hox11/13b expression is restricted to oral ectoderm, endoderm and secondary mesenchyme cells in sea urchin embryos after the gastrula stage.…”
Section: Referencesmentioning
confidence: 99%
“…3a). However, in the embryo, only two Hox genes (Hox7 and Hox11/13b) are expressed (Angerer et al, 1989;Dobias et al, 1996). The expression of Hox7 protein is restricted to the aboral ectoderm, and Hox11/13b expression is restricted to oral ectoderm, endoderm and SMCs in sea urchin embryos after the gastrula stage (Fig.…”
Section: Hox7 and Hox11/13b Are Involved In Pattern Formation In Sea mentioning
confidence: 99%